FLUID DYNAMICS ANALYSIS IN THE DAM BREAK PHENOMENON BASED ON MEASUREMENT SYSTEM - ABDILLAH (NIM : 20216022), HABIBI
The dam break has become one of the disasters that have caused damage to the environment, infrastructure, and human deaths. Understanding of fluid dynamics in the dam break phenomenon is needed so that a plan can be built to minimize the impact. This research was conducted to observe the phenomenon of dam break experimentally and simulation. The process in this study includes literature study, system design, experiment and simulation, data processing, data analysis, and discussion. The things observed in this experiment are fluid wave profiles after the dam break process, fluid thrust on the vertical wall, and fluid flow velocity. Speed measurement system uses the image processing method using high frame rate cameras. To measure the fluid pressure on the vertical wall load sensor is used. The variables that were varied in this study were the initial height of the fluid and the variation of the wall distance. Fluid thrust data, velocity, and wave profile have been obtained and displayed in the form of images and graphs.